2017
DOI: 10.1136/bjophthalmol-2016-310005
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity: screening and treatment in Costa Rica

Abstract: We provide comprehensive data of ROP care in Costa Rica allowing assessment and comparison of screening criteria and protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
(5 reference statements)
1
8
0
Order By: Relevance
“…Studies conducted in high-income countries have shown that infants born at ≥32 weeks are not at risk for developing ROP and most infants born at >28 weeks who develop ROP have a mild disease that spontaneously regressed without treatment 9. The findings of the TR-ROP study were comparable to those from other developing countries and showed that more mature and heavier babies were at risk for severe ROP 10…”
Section: Discussionmentioning
confidence: 68%
“…Studies conducted in high-income countries have shown that infants born at ≥32 weeks are not at risk for developing ROP and most infants born at >28 weeks who develop ROP have a mild disease that spontaneously regressed without treatment 9. The findings of the TR-ROP study were comparable to those from other developing countries and showed that more mature and heavier babies were at risk for severe ROP 10…”
Section: Discussionmentioning
confidence: 68%
“…In a study by Tabarez-Carvajal et al among 3018 premature infants, the incidence of stages 1, 2, 3, 4, and 5 was reported to be 8.34%, 8.78%, 1.9%, 0.03%, and 0.30%, respectively [ 33 ]. In another study by Abdel HA et al, the prevalence of ROP stage 1 was 10.4%, stage 2 was 5.2% and stage 3 was 3.45%, and none of the infants had ROP at stages 4 or 5 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…El Salvador and Guatemala have less than 50% of provinces/regions implementing a programmme (Table 1). 2014, 19 and Colombia uses the national health information system (ASIS) to collect data on the number of live born babies with birth weight <1,999 g with a diagnosis of ROP; in 2014 it was 8.3%. 20 Some countries have assessed their ROP programme in a selected group of NICUs; in 7 units in Rio de Janeiro, Brazil in 2010 to identify the characteristics of preterm infants at risk of ROP, 21 in 6 units in Lima, Peru in 2012, 22 and in 32 units in Mexico in 2015.…”
Section: Plans and Programmesmentioning
confidence: 99%